The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jan.15478
|View full text |Cite
|
Sign up to set email alerts
|

The mental health impact of COVID‐19 on pre‐registration nursing students in Australia: Findings from a national cross‐sectional study

Abstract: Aim The study aimed to measure and describe the mental health impact of COVID‐19 on Australian pre‐registration nursing students. Background The COVID ‐19 pandemic has had a swift and significant impact on nursing students across the globe. The pandemic was the catalyst for the closure of schools and universities across many countries. This necessary measure caused additional stressors for many students, including nursing students, leading to uncertainty and anxiety. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
2
11
1
Order By: Relevance
“…The findings of this QES highlight the importance of welldesigned online or blended learning programmes using digital tools that support interaction and teamwork. Recent studies support our finding that courses can be transformed into effective and efficient high-quality student-centred education, provided that various supporting means for online learning are actively implemented (Berga et al, 2021;Carolan et al, 2020;Kang et al, 2021;Kunaviktikul et al, 2022;Leidl et al, 2020;McGeehin Heilferty et al, 2021;Thirsk et al, 2023;Urban et al, 2022;Usher et al, 2022).…”
Section: Respects Diverse Talents and Ways Of Learningsupporting
confidence: 70%
“…The findings of this QES highlight the importance of welldesigned online or blended learning programmes using digital tools that support interaction and teamwork. Recent studies support our finding that courses can be transformed into effective and efficient high-quality student-centred education, provided that various supporting means for online learning are actively implemented (Berga et al, 2021;Carolan et al, 2020;Kang et al, 2021;Kunaviktikul et al, 2022;Leidl et al, 2020;McGeehin Heilferty et al, 2021;Thirsk et al, 2023;Urban et al, 2022;Usher et al, 2022).…”
Section: Respects Diverse Talents and Ways Of Learningsupporting
confidence: 70%
“…The level of PTSD in our sample is lower than those reported by the studies invested in the initial phase of the COVID-19 outbreak, the prevalence in Spain and China was 26.7 and 44.5%, respectively (19,20). The proportion of the sample reporting lower levels of PTSD than the Australian study (49.4%) (26). Compared to the domestic literature in 2022 (15.42%), the prevalence of PTSD in the study was relatively lower (11.2%) (13).…”
Section: The Prevalence Of Ptsdcontrasting
confidence: 54%
“…Moreover, Thirsk et al (2023) have recently suggested that learning in real clinical learning environments, which includes exposure to a variety of patients, families and communities can enhance the student nurse experience and prepare them to become more experienced, socialized, competent practitioners with a desire to practice in a range of clinical environments. Usher Am et al (2022) concurred with this position and believe that when students lack effective clinical skills training and development of strong clinical decision‐making skills it risks their confidence and increases the risk of near‐miss or clinical errors. As such a blended learning approach should be considered incorporating the best components to deliver the teaching content (Ilankoon et al, 2022).…”
mentioning
confidence: 98%
“…Online teaching and learning has not always been an entirely positive experience, and online learning was negatively experienced by some students and faculty who had poor psychosocial outcomes, reduced motivation and decreased concentration (Usher Am et al, 2022). Through a qualitative meta‐synthesis of students and faculty experience of online teaching and learning, Shorey et al (2022) found that during the pandemic students were overwhelmed by an increased number of assessments, diminished academic achievements and poorer clinical readiness.…”
mentioning
confidence: 99%